Peningkatan Kemampuan Menulis Naskah Drama Dengan Media Audio-Visual Oleh Siswa Kelas XI DPIB SMK Negeri 1 Percut Sei Tuan - Harri Setiawan Simarmata (PT. ALHAFI BERKAH INDONESIA, 2023)
The background of the research problem is that students' ability to write drama scripts is not optimal. One of the factors is the media used by the teacher is not appropriate and is still traditional. To overcome this, it is done by using audio-visual media. The purpose of this study was to improve students' skills in writing drama texts by paying attention to the building blocks of drama performances. The method used in this study was descriptive method, with a classroom action research design. The data collection techniques were library research, observation, and learning. , and tests. The data that has been collected is then analyzed and the results are described. The results obtained are as follows: (1) The steps for using audio-visual media to improve the ability to write drama scripts for class XI DPIB students of SMK N 1 Percut Sei Tuan are divided into three stages of activity, namely preliminary activities, core activities and final activities. (2). There was an increase in students' ability to write drama scripts after using audio-visual media in class XI DPIB students of SMK N 1 Percut Sei Tuan. . Class action research (CAR) was conducted in two cycles, namely cycle 1 and cycle 2. Each cycle experienced an increase in student learning outcomes. At the pre-cycle stage, the percentage of students who achieved learning mastery was 46.43%. Then, in cycle 1, this figure increased to 64.28%. After going through cycle 2, the percentage of students who achieved learning mastery increased again to 82.14%. These results indicate an increase in students' writing skills in writing drama scripts using audio-visual media. That is, the value of student learning outcomes in writing drama scripts from cycle I to cycle II experienced a significant increase.